DYNAMICS OF INDICATORS OF THE BARTHEL’S ACTIVITY INDEX AND RANKIN SCALE AFTER ACUTE CEREBRAL HEMISPHERIC ISCHEMIC STROKE DEPENDING ON TREATMENT METHODS - Pushko, O.O.; Lytvynenko, N.V.; Delva, M.Yu. (World of Medicine and Biology, 2024)
The purpose of the study was to evaluate the dynamics of indicators of Barthel’s activity index and Rankin Scale after acute cerebral hemispheric ischemic stroke and their correlation at different stages of recovery depending on the treatment methods. The study involved 77 patients diagnosed with acute cerebral hemispheric ischemic stroke. The observation period was six months. The study found that in the group of active physical rehabilitation, the average total indicators of functional recovery after 6 months of observation had significantly (p